The Role of Leadership With the Implementation of Patient Safety in Public Health Center Y in Cirebon City - Puspandhani, Mitha Erlisya; Fadila, Erida; Shintami, Rica Arieb (International Journal for Educational and Vocational Studies, 2020)
The application of patient safety is influenced by five factors namely individual factors and nurse performance, work environment factors, patient factors, organizational factors, and external factors. This explanation concludes that patient safety performance as an organization's quality performance is influenced by the role of the leader in it. Leadership is an aspirational power, strength, enthusiasm, and creative moral strength that is able to influence members to change attitudes, so that they come to understand the leader's desires. The behavior of the group or organization becomes the aspirations of the leader. by the interpersonal influence of the leader on his subordinates. In such conditions there is volunteerism or induction of compliance (complience induction) subordinate to the leadership. Especially in an effort to achieve a common goal, so the process of solving the problems that must be faced collectively is needed.Leadership has a function as a mobilizer and coordinator of human resources, natural resources, all funds, and facilities prepared by a group of people who work together to behave in achieving goals. Achieving goals starts from creating high productivity. This condition allows nurses to work as optimal as possible, so that the needs and safety of patients can be met . Program patient safety mentioned above is expected to prevent injury caused by the fault / error due to carry out an act dala m service kesehaatan Interest to determine the relationship of leadership roles with penerapatan patient safety in the inpatient unit PHC Y Cirebon This type of research is descriptive correlative with cross sectional approach, the number of samples were 30 respondents, the research instrument used a questionnaire. Data analysis using chi square test. The results showed that of 30 respondents the majority of respondents stated the role of leadership was good, 17 respondents (56.7%). Most nurses apply patient safety well, that is 56.7% of the 30 respondents. The result of the bivariate analysis found that there was a relationship between the leadership's role and patient safety application in the inpatient room at Puskesmas Y Cirebon City with p value = 0.025 (alpha = 0.05). Recommendations that can be given are interventions needed in the form of providing information to leaders in order to carry out their roles properly, as well as providing training to implementers to implement patient safety properly.